2015
DOI: 10.1128/iai.02814-14
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus pyogenes Malate Degradation Pathway Links pH Regulation and Virulence

Abstract: The ability of Streptococcus pyogenes to infect different niches within its human host most likely relies on its ability to utilize alternative carbon sources. In examining this question, we discovered that all sequenced S. pyogenes strains possess the genes for the malic enzyme (ME) pathway, which allows malate to be used as a supplemental carbon source for growth. ME is comprised of four genes in two adjacent operons, with the regulatory two-component MaeKR required for expression of genes encoding a malate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 58 publications
2
19
0
Order By: Relevance
“…A recent study on group A streptococcus (51) identified malate degradation as a link between pH and virulence. Our findings of increased transcriptional activity of the maeE and maeP genes in ABSA in response to malate are also consistent with the response of group A streptococcus (51).…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…A recent study on group A streptococcus (51) identified malate degradation as a link between pH and virulence. Our findings of increased transcriptional activity of the maeE and maeP genes in ABSA in response to malate are also consistent with the response of group A streptococcus (51).…”
Section: Discussionsupporting
confidence: 77%
“…Therefore, we analyzed whether the growth of ABSA and UPSA strains would differ in a synthetic medium that contained a defined amount of malate. For this, we used SHU as defined in previous studies (56)(57)(58) supplemented with 40 mM malic acid, a concentration consistent with prior studies that have used 30 to 50 mM malic acid in vitro (51,(53)(54)(55)(59)(60)(61)(62). We observed that the growth of ABSA 834 and ABSA 729 was significantly higher than the growth of UPSA 058 and UPSA 714 in SHU (Fig.…”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…The fact that maeK mutants in different species do not activate mae genes in response to the presence of L-malate 18, 22 clearly indicate that MaeK is a functional L-malate sensor. However, it is intriguing how a HK devoid of its ATP-dependent kinase activity can operate in signalling.…”
Section: Discussionmentioning
confidence: 99%
“…In S. pyogenes and L. casei , in addition to L-malate, low pH also induced the expression of maePE 22 . Interestingly, it has been shown that induction by low pH is independent of L-malate but requires a functional MaeK in S. pyogenes 22 .…”
Section: Introductionmentioning
confidence: 96%